2018
DOI: 10.1136/openhrt-2018-000916
|View full text |Cite
|
Sign up to set email alerts
|

Multiple biomarker panel to screen for severe aortic stenosis: results from the CASABLANCA study

Abstract: ObjectiveSevere aortic valve stenosis (AS) develops via insidious processes and can be challenging to correctly diagnose. We sought to develop a circulating biomarker panel to identify patients with severe AS.MethodsWe enrolled study participants undergoing coronary or peripheral angiography for a variety of cardiovascular diseases at a single academic medical centre. A panel of 109 proteins were measured in blood obtained at the time of the procedure. Statistical learning methods were used to identify biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Whilst individual studies have reported on multiple biomarkers [77,78], this is the first systematic review and meta-analysis to date that assesses the association of multiple biomarkers with mortality in a wider population of patients with AS.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst individual studies have reported on multiple biomarkers [77,78], this is the first systematic review and meta-analysis to date that assesses the association of multiple biomarkers with mortality in a wider population of patients with AS.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the overlap in mechanisms behind BNP release, it is non-specific for AS in isolation 57 71. As a result, an approach with multiple biomarkers may provide better insight 64 65 72…”
Section: Emerging Assessment Techniquesmentioning
confidence: 99%
“…Notch may have an important role in aortic valve calcification ( Kostina et al, 2018 ) and the Notch ligand Delta-1 is elevated and associated with mortality in patients with symptomatic aortic stenosis ( Abraityte et al, 2015 ). Elmariah et al suggested that a panel of multiple biomarkers including age, NT-proBNP, vWF, and fetuin-A would be valuable for the identification of high-risk patients with aortic stenosis and for timely valve intervention ( Elmariah et al, 2018 ). MacGrogan et al also suggested that a set of several genes in blood provided a “gene signature” predicting aortic valve calcification ( MacGrogan et al, 2020 ).…”
Section: Biomarkers Of Aortic Valve Calcificationmentioning
confidence: 99%